2021
DOI: 10.3389/fpsyg.2021.703280
|View full text |Cite
|
Sign up to set email alerts
|

“The New State That We Are Building”: Authoritarianism and System-Justification in an Illiberal Democracy

Abstract: The authoritarian personality is characterized by unquestionining obedience and respect to authority. System justification theory (SJT) argues that people are motivated to defend, bolster, and justify aspects of existing social, economic, and political systems. Commitment to the status quo is also a key characteristic of the authoritarian personality. It can be argued that the social context matters for how an underlying latent authoritarian character is expressed. This means that authoritarian regimes could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…In light of the new political populism across Europe, North America and elsewhere, we examined whether a system justification perspective or a social identity model of system attitudes best explains the motivations of people who wanted to retain the existing order or to change it. Findings from our analyses suggest that the motivations for both camps of the political divide are best characterized as rooted in personal and collective interests rather than resulting from a separate system justification motivation (see also in this issue works by Caricati et al, 2021;Carvalho et al, 2021;Degner et al, 2021;Lönnqvist et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…In light of the new political populism across Europe, North America and elsewhere, we examined whether a system justification perspective or a social identity model of system attitudes best explains the motivations of people who wanted to retain the existing order or to change it. Findings from our analyses suggest that the motivations for both camps of the political divide are best characterized as rooted in personal and collective interests rather than resulting from a separate system justification motivation (see also in this issue works by Caricati et al, 2021;Carvalho et al, 2021;Degner et al, 2021;Lönnqvist et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, it refers to the psychological tendency of individuals who usually feel disadvantaged in society, including feeling that their life is more difficult (Kuper and Kuper, 2001). Some research studies have found that system justification was positively associated with socioeconomic status (e.g., Lönnqvist et al, 2021). Compared to individuals with higher incomes, disadvantaged individuals feel that the system cannot meet their needs and that they are unable to change it.…”
Section: Introductionmentioning
confidence: 99%